2016
DOI: 10.1016/j.foodhyd.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive mill wastewater phenolic extract, whey protein isolate and xanthan gum on the behaviour of olive O/W emulsions using response surface methodology

Abstract: Spray-dried polyphenols extracted from olive mill wastewater (OMW) were used to formulate 20% olive oil-in-water (O/W) emulsions stabilised with whey protein isolate (WPI) and xanthan gum at pH 7. The effects of olive biophenol extract (0.9-4.4 mM), whey protein isolate (0.13-0.5 %) and xanthan gum (0.06-0.2 %) on the physical stability (creaming index), viscosity, emulsion droplet size and distribution, primary and secondary oxidation products were assessed over accelerated storage of emulsions. Response s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Additionally, the interactions between all variables had significant effects on this response. MD added to the aqueous phase of O/W emulsions was expected to increase creaming stability, since addition of polymers, such as MD, to the aqueous phase of O/W emulsions at high concentrations increases the viscosity of the continuous phase, resulting in improved emulsion stability (Caporaso et al, 2016a(Caporaso et al, , 2016bFioramonti, Arzeni, Pilosof, Rubiolo, & Santiago, 2015;Klinkesorn et al, 2004;McClements, 2000;Salimi et al, 2015). Polysaccharides are reported to induce flocculation of oil droplets and the formation of a gel-like network that delays creaming (Parker, Gunning, Ng, & Robins, 1995;Udomrati et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the interactions between all variables had significant effects on this response. MD added to the aqueous phase of O/W emulsions was expected to increase creaming stability, since addition of polymers, such as MD, to the aqueous phase of O/W emulsions at high concentrations increases the viscosity of the continuous phase, resulting in improved emulsion stability (Caporaso et al, 2016a(Caporaso et al, , 2016bFioramonti, Arzeni, Pilosof, Rubiolo, & Santiago, 2015;Klinkesorn et al, 2004;McClements, 2000;Salimi et al, 2015). Polysaccharides are reported to induce flocculation of oil droplets and the formation of a gel-like network that delays creaming (Parker, Gunning, Ng, & Robins, 1995;Udomrati et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Emulsifiers used in the present study have also been shown to affect emulsions’ oxidative stability (Haahr & Jacobsen, ; Horn et al., ; Horn, Nielsen, & Jacobsen, ; Nielsen et al., ). Recent efforts reported involve incorporation of phenolic compounds into O/W emulsions stabilized by an emulsifier and a stabilizer to improve the oxidative stability of the emulsions (Caporaso et al., , ). To the authors’ knowledge, the potential of BCD to prevent lipid oxidation in an O/W emulsion, when used in combination with an emulsifier (CITREM) and a stabilizer (MD), has been investigated for the first time in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full factorial designs are often used to study the interaction between temperature and salinity (Likongwe et al., ; Watanabe et al., ), showing the quadratic effects of factors or a combination of optimal factor levels (Jun et al., ). Response surface methodology (RSM) is usefully applied as an effective tool for the optimization of a process when the independent variables can exert a combined effect on the desired response (Caporaso et al., ). RSM has been previously applied by other researchers to study combination of temperature and salinity in the early development of aquatic animals (Wang et al., ; Darvishi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…RSM has been previously applied by other researchers to study combination of temperature and salinity in the early development of aquatic animals (Wang et al., ; Darvishi et al., ). Among the advantages of its application, RSM allows the design of a comprehensive model describing the characteristics of a system, by minimizing the number of experiments required (Caporaso et al.,). Central Composite Design (CCD) is one of the most common forms of RSM.…”
Section: Introductionmentioning
confidence: 99%